Perceived synonyms in "al-mufradat fi gharib Al-Quran" by Al-Raghib Al-Asfahani - Dameng, Sobri (2011)
The study is aims at exploring the topic of perceived synonymy in ‘al-Mufradat fi Gharib al-Quran’ by al-Raghib al-Asfahani. The research sets to find out the relationship between words and their lexical or primary meaning and subsequently look for any possibility of their differences in other semantic aspects. It explores some words which were taken by mistake as synonyms and discusses the views of the proponents of synonyms and those who opposed to its reality. The importance of the study lies in the fact it deals with words as part of the human communication thus discovering the wealth of language in describing detailed aspects of meaning as well as the terminologies that describe concepts. The study used the library research method: previous studies and references on the matter were gathered, and analytical method was carried out to zoom in on the words which were taken mistakenly as pairs of synonyms. The study found out that the Arabic language scholars are of different views regarding the definition of synonyms,consequently, there were those who argued in favor of its reality and those who opposed it. It also found that many of the synonyms as proposed in the book were not full synonyms, as they were different in their aspects of connotation and meaning field. The study also concluded that 270 meaning entries in the book which have more than two different words were true synonyms.